2007
DOI: 10.1111/j.1754-4505.2007.tb00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health needs and barriers to dental care in hospitalized children

Abstract: The goal of this study was to examine the oral health status and utilization of dental care reported by hospitalized children. A bedside oral examination was performed on hospitalized children. Past dental treatment and current oral health needs were assessed. The mean age (+/- SD) of 120 enrolled patients was 6.7 (+/- 2.9) years (range 3 to 12); 60% were males. The age of the patients' first dental office visit was 3.5 +/- 1.8 years, with 28% having never seen a dentist. Unmet oral health needs (e.g., untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
2
19
0
2
Order By: Relevance
“…Like other studies that have found CSHCN’s access to oral health services challenged by resource constraints, 41 administrative burdens, 42 lack of available dentists, 17, 43–44 and low demand from parents, 45 our study identified similar barriers. Additionally, all the organizations brought up fluoride as a preventive oral health tool but did not uniformly recommend fluoride to families of CSHCN.…”
Section: Discussionsupporting
confidence: 80%
“…Like other studies that have found CSHCN’s access to oral health services challenged by resource constraints, 41 administrative burdens, 42 lack of available dentists, 17, 43–44 and low demand from parents, 45 our study identified similar barriers. Additionally, all the organizations brought up fluoride as a preventive oral health tool but did not uniformly recommend fluoride to families of CSHCN.…”
Section: Discussionsupporting
confidence: 80%
“…Untreated caries was found in 42% of subjects and soft tissue abnormalities in 59%. No statistically significant differences were found between the subjects who were chronically ill or acutely ill. Caregivers of subjects with chronic medical conditions were more likely to report barriers to dental care than caregivers of subjects with acute conditions 2 …”
Section: Introductionmentioning
confidence: 98%
“…A literature search found very few publications specific to oral health of pediatric patients who were hospitalized. Relevant literature included: descriptive studies, 1‐3 case reports, 4,5 and case series 6 related to oral problems of children who were hospitalized. The American Academy of Pediatric Dentistry (AAPD) guidelines on Dental Management of Pediatric Patients Receiving Chemotherapy, Hematopoietic Cell Transplantation, and/or Radiation, 7 and the American Academy of Pediatrics (AAP) and AAPD policy on the dental home 8,9 are also applicable to this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Intellectual and developmental disability (IDD) children face additional barriers to receiving dental care and may be at higher risk for dental disease; they utilise preventive dental services at the same rate as non-IDD children. 26 Children with chronic medical conditions reported barriers to receiving dental care more often (24%) than children with acute medical conditions (3.5%). A high prevalence of unmet oral health needs and soft tissue abnormalities was identified in a hospitalised pediatric population.…”
mentioning
confidence: 98%